Kontribusi Usaha Kambing Bligon Dalam Mewujudkan Ketahanan Pangan Berbasis Ternak Wilayah (Studi di Daerah Pesisir Kabupaten Bantul, DIY) - Haryanto, Bambang; Wardi, Wardi; Puspito, Sigit; Yano, Aan Andri; Pratiwi, Nugraheni Nur; Bhermana, Andy; Sulistyaningsih, Yoshi Tri (Jurnal Ketahanan Nasional, 2024)
ABSTRACT Bligon goats, as one of the local livestock resources, had significant potential to improved the welfare of coastal communities in Bantul Regency. The aim of the research was to analyzed the contribution of the viability of the bligon goat business in realizing food resilience, livestock empowerment, and the foundations of national resilience in the coastal areas of Bantul Regency. The research was conducted in Bantul Regency at two kapanewons which represent coastal areas, namely Sanden and Srandakan. This study used an approach to economic conditions over the past year. The calculations carried out included total production, added value, the function of livestock as savings, insurances and fertilizer producers. The average age of farmers in the research location was 53 years 10 months, with an average of 13 years of farming experience and an average of 7 goats. The results of calculating the Net Benefit-Cost Ratio (B/C), Payback Period (PP), and Internal Rate of Return (IRR) in calculating the financial feasibility of the Bligon goat farming business in coastal areas showed that this business was worthy of development. The development of Bligon goat cultivation could be used in efforts to alleviated poverty in the community and supported sustainable economic growth in the coastal areas of Bantul Regency. The sustainability of this economic dimension was expected to make a positive contribution to food resilience and national resilience by encouraging an increase in the number of farmers and goats.